MENADŽMENT RIZIKA I BEZBEDNOSTI SPORTSKOG DOGAĐAJA - Srećko Novaković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The acquired information and knowledge that the public in the sport events: from heterogeneous sport audience, media and sport superstructure to sports organizations relate to the security in a passive way, in an expectation that the risk of security incidents should be taken up by other security structures demand that the relationship police - sport should be changed and that the security of sport events should be primary part of sport, especially of clubs and other sports organizations. To achieve that the change a new attitude towards the security in sports organizations in necessary, in the system of values and with respect to the investment in the security of sport facilities. The first necessary step is an educational effort of sport associations and organizations that will induce the change towards the better appreciation of the security in sport.